Investigating the relationship between horizontal forest structure and fire behavior using a physics-based fire model - Burke, Conamara S., author; Hoffman, Chad, advisor; Mell, William, committee member; Amidon, Timothy, committee member (Colorado State University. Libraries, 2017)
Silvicultural treatments are increasingly being implemented across the Western US in fire-prone forests as a way to simultaneously reduce fire hazard while also increasing horizontal structural heterogeneity (tree spatial patterns). However, it is poorly understood how fire behavior is impacted by treatment designs that incorporate tree clumping spatial configurations that mimic patterns found within the historic structural ranges of forests frequented by low to mixed severity fire. The Wildland Urban-Interface Fire Dynamics Simulator (WFDS), a physics-based fire behavior model, was used to better understand the effect that heterogeneous horizontal forest structure has on fire behavior. Fire behavior across seven treated ponderosa pine forests with different spatial patterns were simulated and compared to each other, and to an untreated scenario. All forest simulations were also burned under three different wind speeds and two surface fuel loading levels to better evaluate fuel treatment effectiveness across a range of conditions. Results indicate that the removal of surface fuels in treated stands was the most effective method for reducing the percent of canopy consumption and rates of fire spread, especially under high wind velocity conditions. This study found that variations in horizontal forest structure between treated forest scenarios had a minimal effect on driving differences in fire behavior, thus forest managers should be more concerned with increasing horizontal structural heterogeneity for ecological objectives rather than implementing such treatments to reduce the potential for hazardous fire behavior. Future research should focus on determining how vertical structural complexity interacts with horizontal structure to influence fire behavior.